Aceh Besar تحليل بناء بنود الإختبار لمادة اللغة العربية بمعهد روح الإسلام أناك بنجسا - Meilina, Sheila; Ninoersy, Tarmizi; Hayati, Salma (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
So far, the making of evaluation question for Arabic language lessons at MAS Ruhul Islam Anak Bangsa Aceh Besar has not been conducted in-depth qualitative research according to competency standards, especially in item construction, before being tested on students. The teacher designs the items only based on the difficulty level of the questions without looking at other aspects. Therefore, the aim of this research is to describe the accuracy of the construction of multiple choice items in Arabic lessons in class XI MAS 2019/2020 using descriptive statistical analysis methods. This type of research is qualitative research, the population in this research is 50 multiple choice questions in Arabic that designed by the teacher for class XI MAS Ruhul Islam Anak Bangsa 2019/2020. The sample of this research is 25 questions from the population and the sampling uses simple random sampling technique. Data collection techniques of this research are documentation. Qualitative analysis techniques was carried out using a format (table) designed by the researcher. The results of this study were based on samples, there were 16 questions in accordance with the research aspect of the accuracy of the construction of multiple choice items, while 9 other questions were not in accordance with the aspects of the accuracy of the construction of multiple choice items. When viewed from the aspect of construction accuracy in the total sample size, it is found that 8 aspects have been dominantly owned by all samples and 4 other aspects are not owned by the sample. And it is known that the 50 questions designed by the teacher belong to the types of distracters questions.